Negative association between body roundness index and constipation: insights from NHANES - Lingting Chen; Huirong Xiao; Xuchao Yu; Bingbin Huang; Sirong Guo; Ting Yuan; Siyang Deng (Journal of Health, Population and Nutrition)
Abstract Backgrounds The relationship between body roundness index (BRI), a metric that distinguishes heterogeneity in fat distribution, and constipation is unclear. This study is the first to investigate the association between BRI and constipation based on the National Health and Nutrition Examination Survey (NHANES) in the United States, providing a new perspective on the mechanisms of obesity-related gastrointestinal dysfunction. Methods This cross-sectional study utilized data from the NHANES conducted between 2005 and 2010. Constipation was diagnosed based on the Bristol Stool Form Scale (BSFS). Weighted logistic regression models were employed to assess the association between BRI and constipation prevalence. Restricted cubic splines (RCS) and piecewise linear regression models were applied to evaluate non-linear relationships between BRI and constipation. Propensity score matching (PSM) was implemented to match constipated and non-constipated populations with similar baseline characteristics. Subsequent analyses were conducted to investigate the correlation between BRI and constipation. Results A total of 12,732 eligible participants were included. A negative correlation was observed between BRI and constipation prevalence, with an adjusted odds ratio (OR) of 0.87 (95% CI: 0.80, 0.95) after controlling for all covariates. When BRI was categorized into quartiles (Q1-Q4), both Q3 and Q4 groups exhibited significantly reduced constipation risk compared to Q1 (OR = 0.72, 95% CI: 0.54–0.97; OR = 0.63, 95% CI: 0.46–0.87). The RCS regression model revealed a linear inverse association between BRI and constipation risk (nonlinearity test P = 0.083). Subgroup analyses identified significant interaction effects of BRI with age, alcohol consumption status, and hypertension on constipation risk (interaction P < 0.05). Post PSM, constipation patients demonstrated higher BRI levels than non-constipation counterparts (P = 0.013). Conclusion An inverse association was observed between BRI and constipation risk in U.S. adults, suggesting that lower BRI levels may correlate with raised constipation incidence. This underscores the critical importance of maintaining optimal BRI levels for constipation prevention. Further research is warranted to elucidate the underlying mechanisms governing this association.